Clinically important intracranial abnormalities in children presenting with first focal seizure - Kasap, Tuba; Tekşam, Özlem; Turanlı, Güzide; Konuşkan, Bahadır; Oğuz, Kader Karlı; Haliloğlu, Göknur; Yalnızoğlu, Dilek (The Turkish Journal of Pediatrics, 2023)
Background. Management of pediatric patients presenting with first seizure is challenging, especially with regards to emergent neuroimaging. The rate of abnormal neuroimaging findings is known to be higher in focal seizures than in generalized seizures, but those intracranial abnormalities are not always clinically emergent. In this study, we aimed to determine the rate and indicators for clinically important intracranial abnormalities that change acute management in children presenting with a first focal seizure to the pediatric emergency department (PED). Methods. This study was conducted retrospectively in the PED at a University Children`s Hospital setting. The study population consisted of patients aged between 30 days and 18 years with first focal seizure and who had emergent neuroimaging at the PED between the years 2001 and 2012. Results. There were 65 eligible patients meeting the study criteria. Clinically important intracranial abnormalities requiring emergent neurosurgical or medical intervention were detected in 18 patients (27.7%) at the PED. Four patients (6.1%) underwent emergent surgical procedures. Seizure recurrence and the need for acute seizure treatment in the PED were significantly associated with clinically important intracranial abnormalities. Conclusions. Neuroimaging study yielding of 27.7% shows that first focal seizure must be evaluated meticulously. From the emergency department`s point of view; we suggest that first focal seizures in children should be evaluated with emergent neuroimaging, if possible with magnetic resonance imaging. Especially patients with recurrent seizures at presentation requires more careful evaluation.
Keywords: children; emergent neuroimaging; first focal seizure; first seizure; important intracranial abnormalities; seizure recurrence